Linkage disequilibrium of plasminogen polymorphisms and assignment of the gene to human chromosome 6q26-6q27 - Murray, Jeffrey C. (1987)
Linkage disequilibrium was observed between newly identified DNA polymorphisms and a previously described protein polymorphism for plasminogen. This finding implies that the two types of polymorphisms describe variation at the same locus. The plasminogen gene was mapped to chromosomal bands 6q26-q27 using somatic-cell hybrids and in situ hybridization. Linkage disequilibrium between protein and DNA polymorphisms has utility in substituting for protein typing in instances where only DNA samples are available, such as from deceased individuals or extinct species. The technique may be useful when cross-hybridizing sequences make the interpretation of Southern blot patterns difficult and may obviate the need for extensive DNA sequencing. In some cases, disequilibrium may provide information useful for determining the appropriate direction for chromosome walks from a marker locus to a target locus.